Financial attributes, corporate governance and tax avoidance among Malaysian listed companies: The moderating effect of managerial ownership - Salleh, Abdul Ahad AKS Mohd; Kassim, Aza Azlina Md; Abubakar, Ahmad Haruna (Edelweiss Applied Science and Technology, 2025)
Governments rely on corporate tax as a primary source of revenue. Nevertheless, premeditated conduct by corporations to invade tax via avoidance strategies directly hinders the nations growth. This study investigates specifically the relationship between selected financial attributes (profitability and leverage) and corporate governance attributes (board size, director competency, the presence of female directors, director remuneration, and CEO duality) towards corporate tax avoidance among companies listed on Bursa Malaysia's main market. Additionally, the research explores the moderation effect of managerial ownership on the relationships between these variables. The study uses panel data from 300 publicly traded Malaysian companies from their annual reports and financial databases in 2021, 2022, and 2023. Panel data regression with Panel Corrected Standard Errors (PCSE) is used to manage autocorrelation and heteroscedasticity, based on agency theory and tax planning theory. The study found a substantial negative correlation between profitability measured by return on equity. However, leverage exhibited strong positive correlation with corporate tax avoidance. Managerial Ownership considerably mitigated the effects of board size, number of female director representation in the company, and director remuneration on corporate tax avoidance. Developing market policymakers and regulators can use these findings to their advantage in their pursuit of ethical tax governance.